Recruitment and talent acquisition process of Standard Chartered Bank Ltd. - Khan, Md. Asadujjaman (BRAC University, 2016)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2015.